Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ma13122736
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Nanoparticulate Hydroxyapatite Powders as Fillers in Polyacrylate Bone Cement—A Comparative Study

Abstract: Acrylate polymer-based bone cements constitute the most popular bonding agents used in regenerative surgery. Due to their inferior biocompatibility, however, these materials are often enriched with ceramic additives including hydroxyapatite (HAp). The aim of this paper was to perform a comparative study of the acrylate cements filled with different content (3–21%) of nano- and microscale hydroxyapatite. The work concerns a comparison of times and temperatures of the cross-linking reaction, as well as morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Szymanowski and coworkers saw similar results when comparing PMMA‐based cements with the addition of HA micro‐ and nanoparticles. [ 58 ] They observed that an increased weight percentage of microparticle HA of up to 21% within the polymer matrix resulted in decreased polymerization temperatures. Notably, nanoparticle HA did not affect the polymerization temperature within their scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…Szymanowski and coworkers saw similar results when comparing PMMA‐based cements with the addition of HA micro‐ and nanoparticles. [ 58 ] They observed that an increased weight percentage of microparticle HA of up to 21% within the polymer matrix resulted in decreased polymerization temperatures. Notably, nanoparticle HA did not affect the polymerization temperature within their scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…In the sections above, strong evidence has already been presented for the feasibility of using hydroxyapatite as a basis for synthetic compositions and materials that can potentially have all the required properties as an alternative to autologous grafts. This is also supported by the use of hydroxyapatite bioceramics in current clinical practice in solid, granular, powdered, porous and composite forms [106][107][108][109]. The latter form attracts special attention because being native bone tissue, bone autografts are composites [110,111].…”
Section: Semisynthetic and Synthetic Bone Substitutesmentioning
confidence: 93%
“…They influence other special properties of selected materials, such as optical properties or biocompatibility [70,71]. The nanoparticles affect not only the final properties but in many cases also processing properties in traditional technologies as well as in modern ones, such as additive manufacturing [48,[72][73][74][75][76]. They allow us to obtain better quality products most effectively.…”
Section: Area Of Applications Of Nano-additives-influence On Material...mentioning
confidence: 99%
“…It is very interesting for the development of sustainable power sources/sensing tools [68] or for use for sensors for health monitoring. The nanomaterials are also widely applied in medicine, including polymerbased bone cement and drug delivery systems, where the possibility of encapsulation of substances inside nanoparticles is used [31,72].…”
Section: Area Of Applications Of Nano-additives-influence On Material...mentioning
confidence: 99%